THE GIS APPLICATION IN SMARTPHONE FOR TOURISM - Mohamad, Azlizan Adila; Pugi, Noorsazwan Ahmad; Zainol, Halmi (MATTER: International Journal of Science and Technology, 2016)
Tourism industry is one of the important economic resources in Malaysia. Tourists from all over the world come to Malaysia to enjoy the beauty of this scenic and tropical country. Accordance to government’s efforts in promoting ‘Visit Malaysia’, facilities and development of tourist places are rapidly developed. Due to this matter, the data available should be updated to ensure travelers receive the updated and accurate information of Malaysia. Common approach for field data collection was carried out using pen and papers that requires the field data collector to bring the map to the field and mark the data on the map. With the advance of technology, integration of smartphone and Geographic Information System (GIS) become the popular approach in field data collection. The purpose of this paper is to identify interesting places and hotels in Bandar Hilir, Malacca using GIS mobile data collection. The method of the research can be divided into three stages such as planning the data field, data acquisition, and database development. The planning stage focuses on choosing data collection materials. The data acquisition stage is more on field data collection process and database development concentrates on the creation of a tourism database. ArcGIS software will be used for the study. The application of GIS can be very useful in the tourism industry and offers the tremendous opportunity in order to ensure better services and life quality.